Formulation of a Novel Hesperetin-Loaded Nanoemulsion and Its Promising Effect on Osteogenesis - Maria Júlia Mancim-Imbriani; Jonatas Lobato Duarte; Leonardo Delello Di Filippo; Letícia Pereira Lima Durão; Marlus Chorilli; Denise Madalena Palomari Spolidorio; Patricia Milagros Maquera-Huacho (MDPI AG, 2024)
Alternative therapies associating natural products and nanobiotechnology show new perspectives on controlled drug release. In this context, nanoemulsions (NEs) present promising results for their structural design and properties. Hesperetin (HT), a flavonoid mainly found in citrus fruits, presents highlighted bone benefits. In this context, we developed a hesperetin-loaded nanoemulsion (HT-NE) by sonication method and characterized it by dynamic light scattering, analyzing its encapsulation efficiency, and cumulative release. The biocompatibility in human osteoblasts Saos-2-like was evaluated by the cytotoxicity assay and IC50. Then, the effects of the HT-NE on osteogenesis were evaluated by the cellular proliferation, calcium nodule formation, bone regulators gene expression, collagen quantification, and alkaline phosphatase activity. The results showed that the formulation presented ideal values of droplet size, polydispersity index, and zeta potential, and the encapsulation efficiency was 74.07 ± 5.33%, showing a gradual and controlled release. Finally, HT-NE was shown to be biocompatible and increased cellular proliferation, and calcium nodule formation, regulated the expression of Runx2, ALPL, and TGF-β genes, and increased the collagen formation and alkaline phosphatase activity. Therefore, the formulation of this NE encapsulated the HT appropriately, allowing the increasing of its effects on mechanisms to improve or accelerate the osteogenesis process.